Baseline adherence, socio-demographic, clinical, immunological, virological and anthropometric characteristics of 242 HIV positive patients on ART in Malaysia - Abiola, Abdulrahman Surajudeen; Gyanchand Rampal, Lekhraj Rampal; Othman, Norlijah; Ibrahim, Faisal; Kadir @ Shahar, Hayati; P. Radhakrishnan, Anuradha (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2015)
Adherence to antiretroviral therapy (ART) prevents disease progression, and the emergence of resistant mutations. It also reduces morbidity, and the necessity for more frequent, complicated regimens which are also relatively more expensive. Minimum adherence levels of 95% are required for treatment success. Poor adherence to treatment remains a stumbling block to the success of treatment programs. This generates major concerns about possible resistance of the human immunodeficiency virus (HIV) to the currently available ARVs. This paper aims to describe baseline results from a cohort of 242 Malaysian patients receiving ART within the context of an intervention aimed to improve adherence and treatment outcomes among patients initiating ART. A single-blinded Randomized Controlled Clinical Trial was conducted between January and December, 2014 in Hospital Sungai Buloh. Data on socio-demographic factors, clinical symptoms and adherence behavior of respondents was collected using modified, pre-validated Adult AIDS Clinical Trials Group (AACTG) adherence questionnaires. Baseline CD4 count, viral load, weight, full blood count, blood pressure, Liver function and renal profile tests were also conducted and recorded. Data was analyzed using SPSS version 22 and R software. Patients consisted of 215 (89%) males and 27 (11%) females. 117 (48%) were Malays, 98 (40%) were Chinese, 22 (9%) were Indians while 5 (2%) were of other ethnic minorities. The mean age for the intervention group was 32.1 ± 8.7 years while the mean age for the control group was 34.7 ± 9.5 years. Mean baseline adherence was 80.1 ± 19.6 and 85.1 ± 15.8 for the intervention and control groups respectively. Overall mean baseline CD4 count of patients was 222.97 ± 143.7 cells/mm³ while overall mean viral load was 255237.85 ± 470618.9. Patients had a mean weight of 61.55 ± 11.0 kg and 61.47 ± 12.3 kg in the intervention and control groups, respectively. Males account for about 90% of those initiating ART in the HIV clinic, at a relatively low CD4 count, high viral load and sub-optimal medication adherence levels at baseline.